1994
DOI: 10.1115/1.2919409
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzing Ratings for Multiattribute Design Decision-Making

Abstract: Early in the design process, problems can arise when information is incomplete and goals are not known precisely. When preliminary design evaluation is approached as a multiattribute decision-making problem, both the levels of attributes and their relative importance can be treated as fuzzy numbers elicited from the designer. However, information regarding estimated attribute levels might be lost in limiting the designer to the standard universe of discourse. Another problem is that the attribute weights might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…In Hsiao (1998), both weights of objectives and performance levels are quanti-® ed with the membership functions of fuzzy sets. However, contrary to Thurston and Carnahan (1992) and Carnahan et al (1994) in which the overall desirability of an 1149 NFWA method applied to engineering design evaluation alternative is fuzzy (a fuzzy number), representing its imprecision, the scores assigned during the evaluation process are crisp numbers (degrees of membership of fuzzy numbers). Therefore, this approach is less powerful and credible, as the results do not represent the imprecision of the judgements.…”
Section: Related Workmentioning
confidence: 94%
See 1 more Smart Citation
“…In Hsiao (1998), both weights of objectives and performance levels are quanti-® ed with the membership functions of fuzzy sets. However, contrary to Thurston and Carnahan (1992) and Carnahan et al (1994) in which the overall desirability of an 1149 NFWA method applied to engineering design evaluation alternative is fuzzy (a fuzzy number), representing its imprecision, the scores assigned during the evaluation process are crisp numbers (degrees of membership of fuzzy numbers). Therefore, this approach is less powerful and credible, as the results do not represent the imprecision of the judgements.…”
Section: Related Workmentioning
confidence: 94%
“…In the former, the alternative with the highest fuzzy rating is selected as the`best' ; in the latter, the alternative selected is which is closest to a fuzzy goal. Others, such as Carnahan et al (1994), Chen (1996), Khoo and Ho (1996), Zhou (1997Zhou ( , 1998 and Wang (1999), have followed a similar procedure in engineering design evaluation and quality function deployment (QFD). In these applications, fuzzy numbers characterizes the linguistic terms, and the overall desirability is calculated by the FWA without the extended division.…”
Section: Related Workmentioning
confidence: 98%
“…In this respect, Thurston and Carnahan (1992) stated that fuzzy set theory could be applied to the early stage of preliminary design evaluation under multiple attributes or in situations based on semantic assessment of relative performance levels. Many researchers (Carnahan, Thurston, & Liu, 1994;Khoo & Ho, 1996;Sun, Kalenchuk, Xue, & Gu, 2000;Tsai & Hsiao, 2004;Wang, 2001) have successfully used fuzzy sets in engineering design evaluation. More recently, Huang, Bo, and Chen (2006) had integrated fuzzy sets with genetic algorithms and neural networks to formulate an integrated approach for design concept generation and evaluation.…”
Section: Previous Workmentioning
confidence: 99%
“…Thurston and Carnahan (1992) indicated that fuzzy set theory could be applied in design concept evaluation in situations based on linguistic judgments. Many researchers (Carnahan, Thurston, & Liu, 1994;Khoo & Ho, 1996;Sun, Kalenchuk, Xue, & Gu, 2000;Tsai & Hsiao, 2004) have successfully applied fuzzy sets in design concept evaluation. Huang, Bo, and Chen (2006) proposed an integrated approach which combined fuzzy sets with genetic algorithms and neural networks for supporting design concept evaluation, but this approach lacked efficiency in the real world due to its complex algorithm structures and lengthy training process.…”
Section: Related Workmentioning
confidence: 99%